“I Want That Money Saved for ‘Real’ Victims”: Homicide Detectives’ Perceptions of Victims and Impacts on Advocacy and Services for Loss Survivors - Wesely, Jennifer K. (Homicide studies, 2024)
Those who lose a loved one to homicide are considered crime victims, and accordingly may be eligible for state services and compensation. Yet institutionalized constructs about good/innocent and bad/guilty victims can trigger law enforcement agents’ presumptions of how deserving a homicide loss survivor is of resources, responsiveness and support. These attitudes can impact discretionary decision-making about assistance for survivors. Using qualitative in-depth interviews with Homicide Unit and Victim Services Unit personnel at one agency, this study explores these perceptions and their impacts on advocacy for homicide loss survivors. Ultimately, there are justice implications for this population.